A linked modelling framework to explore interactions among climate, soil water, and land use decisions in the Argentine Pampas. (January 2019) - García, Guillermo A.; García, Pablo E.; Rovere, Santiago L.; Bert, Federico E.; Schmidt, Federico; Menéndez, Ángel N.; Nosetto, Marcelo D.; Verdin, Andrew; Rajagopalan, Balaji; Arora, Poonam; Podestá, Guillermo P.
Abstract: In flat environments, groundwater is relatively shallow, tightly associated with surface water and climate, and can have either positive and negative impacts on natural and human systems depending on its depth. A linked modelling and analysis framework that seeks to capture linkages across multiple scales at the climate/water/crop nexus in the Argentine Pampas is presented. This region shows a strong coupling between climate, soil water, and land use due to its extremely flat topography and poorly developed drainage networks. The work describes the components of the framework and, subsequently, presents results from simulations performed with the twin goals of (i) validating the framework as a whole and (ii) demonstrating its usefulness to explore interesting contexts such as unexperienced climate scenarios (wet/dry periods), hypothetical policies (e.g., differential grains export taxes), and adoption of non-structural technologies (e.g., cover crops) to manage water table depth. Highlights: We explored climate, soil water, and land use interactions in the Argentine Pampas. A linked modelling framework was implemented to explore the climate/water/crop nexus. The modelling framework was conceptually validated as a whole. Simulation of interesting and complex scenarios proved the framework usefulness. Adoption of cover crops can reduce the risk of waterlogging and flooding.